Valorizacija prometnog povezivanja jadranske obale u funkciji razvoja inozemnog turizma - BARIČEVIĆ, Hrvoje (Promet - Traffic&Transportation, 2026)
EVALUATION OF TRAFFIC LINKS IN COSTAL AREA IN THE SERVICE OF TOURIST TRADE DEVELOPMENT The author draws the attention to huge potentials of originating tourism of the EEC member states with more than 320 million custom that still may to a considerable extent be more channelled to our coast. This sets an indispensable requirement of near-future construction and modernization of traffic routes along the coast and leading to the coast, in particular the Adriatic highway and roads listed in the Osin Agreement in conjunction with corresponding access roads.